Association of Atlanto-Occipital Dislocation, Retroclival Hematoma, and Hydrocephalus: Management and Survival in a Pediatric Patient - Lee, Isaac L.; Vasquez, Luis F.; Tyroch, Alan H.; Trier, Todd T. (Journal of Neurological Surgery Reports, 2017)
Atlanto-occipital dislocation (AOD) is an injury with high morbidity and mortality. We present a case of survival of a pediatric patient with the diagnoses of AOD, retroclival hematoma, and resulting hydrocephalus. The patient's cervical spine was stabilized until occipital-cervical fusion provided definitive treatment, and the hydrocephalus was treated with a ventriculostomy. The patient survived with no neurological deficits. A better understanding and awareness of the radiologic criteria of AOD will lead to earlier recognition of AOD and improved outcomes, even in the presence of complications from AOD. Surgical fixation should be used for definitive treatment of injuries with AOD.
Keywords: atlanto-occipital dislocation; retroclival hematoma; hydrocephalus; pediatric trauma